Medical students’ perception of assessment and its effects on their learning in Dubai: a convergent mixed methods study - Khalaf, Eman; Ennab, Farah; Otaki, Farah; Guraya, Shaista Salman; Amir-Rad, Fatemeh; Khan, Erum; Lakhtakia, Ritu (Frontiers in Medicine, 2025)
BackgroundEnhanced learning is achieved when assessments are effectively designed in alignment with the learning objectives and supported by ongoing research in the field. Although it is universally acknowledged that assessments are essential in medical education, little is known about assessment policy and characteristics, and its influence on learning and teaching in medical schools in the Middle East and North Africa region (MENA). The purpose of this study is to investigate the perception of medical students of the assessment method implemented in a medical school in Dubai, United Arab Emirates.MethodsA convergent mixed methods study design was employed. Quantitative and qualitative data were independently collected and analyzed. The quantitative component comprised a cross-sectional observational survey design where a tailormade survey with a five-point Likert-type scale was administered to 87 undergraduate medical students. The corresponding quantitative data was analyzed using the Statistical Package for Social Sciences (SPSS, version 27.0). As for the qualitative data, it was collected through a series of focus group sessions aimed at exploring students’ perception of assessment and its impact on their learning. The corresponding analysis was inductive, following the six-step approach introduced by Braun and Clarke. Following that, merging of the information brought about from the two sources generated meta-inferences, which raised the validity of the study’s findings.ResultsThe percentage of the total average of agreement of the current assessment method efficacy, according to a tailormade survey protocol of 28 components, measured using a five-point Likert-type scale, was 62.24%. This percentage was calculated by dividing the overall mean (i.e., 87.13) by 140 since it is the maximum possible value (i.e., five of the Likert-type scale multiplied by 28 components) and multiplying it by 100. The inductive thematic analysis of the data, collected via focus group sessions, yielded a novel conceptual framework: “Medical Students” Take on Assessment Method’, with two overarching themes: Development Process and Consequences. Within the Development Process theme, two categories emerged: Assessment plan and Student support. As for the Consequences theme, it included three other categories: Output, Outcomes, and Impact. Lastly, the following four meta-inferences emerged from integrating the quantitative with the qualitative analysis findings: Processual perspective, Learners’ reaction, Inclusiveness, and Ripple effects.ConclusionThis study reinforced the importance of effectively assessing medical students’ competences while maximizing the learning value of the encapsulating assessment method. It showed that it is not about making choices around discrete aspects of assessment, but rather to consider an assessment method holistically as dynamic processes with several moving parts. Ideally, assessment methods should be designed, implemented, and maintained in ways that would maximize their learning value, taking into account the corresponding context and learners’ perception.